3D seismic responses of a long lined tunnel in layered poro-viscoelastic half-space by a hybrid FE-BE method. (May 2020) - Zhu, Jun; Li, Xiaojun; Liang, Jianwen
Abstract: This paper aims to study the seismic responses of a long lined tunnel embedded in a water-saturated poro-viscoelastic half-space, with focus on wave passage effects. The poro-viscoelastic half-space is modeled by the Biot's theory and the soil nonlinearity is considered via an equivalent linear approach. The seismic responses of the tunnel structure are simulated by a 2.5D hybrid FE-BE method. A total of 72 cases of different incident angles for plane SV- and P1-waves are simulated, in order to conduct a systematic study on the tunnel seismic responses, in terms of longitudinal internal forces and strains, as well as seismic pore pressure and soil stresses. It is shown that the spatial variation of earthquake ground motion due to wave passage effects results in considerable longitudinal internal forces of the tunnel lining, which cannot be overlooked for seismic design. The responses of the tunnel depend on both the horizontal and vertical incident angles of the seismic waves. It is also shown that the 2D scenario with perpendicularly incident SV-waves, which is commonly considered in engineering practice, may lead to nonconservative seismic design, especially for tunnels in saturated soil.